Ambivalent Sexism, Interpersonal Relationships and Attributional Complexity_x000D_ of School Counselors in Istanbul - KENAN, SEYFİ (My University, 2021)
Since school counselors became an internal part of the school system, they are responsible forpromoting psychological and mental health of their students as well as providing guidance for them. In orderto fulfill these responsibilities, school counselors are expected to have empathetic, inclusive, democratic, andegalitarian attitudes. As a repercussion of these required such attitudes, the school counselors are expected totreat every person equally regardless of their gender, race, and lifestyle, and not to discriminate people basedon their attributions, and maintain healthy interpersonal relationships within the counseling settings. Thus, theaim of this research is to examine school counselors’ ambivalent sexism in the context of interpersonalrelationships and attributional complexity. For this purpose, the relationships between interpersonalrelationship dimensions (empathy, approval dependence, trust others, and emotional awareness), ambivalentsexism, and attributional complexity were analyzed. Ambivalent Sexism Inventory, Attributional ComplexityScale, and Scale of Interpersonal Relationship Dimensions were used as instruments. With a sample of 340school counselors from Istanbul, our findings indicate that ambivalent sexism, interpersonal relationshipdimensions, and attributional complexity are correlated with each other on different levels. Furthermore, wefound some unexpected results such as a high level of sexism and a low level of empathy accompanied bypositive causal relationships between ambivalent sexism and empathy and emotional awareness. In the end,the findings of this study essentially aspire to raise awareness about the issue of sexism among prospective andworking school counselors in addition to stressing the need for boosting empathetic attitudes.